Quantum Spectrum of Tachyonic Black Holes in a Brane-Anti-Brane System - Aroonkumar Beesham (Advances in High Energy Physics)
Recently, some authors have considered the quantum spectrum of black holes. This consideration is extended to tachyonic black holes in a brane-anti-brane system. In this study, black holes are constructed from two branes which are connected by a tachyonic tube. As the branes come closer to each other, they evolve and make a transition to thermal black branes. It will be shown that the spectrum of these black holes depends on the tachyonic potential and the separation distance between the branes. By decreasing the separation distance, more energy emerges and the spectrum of the black hole increases.